Mechanical Propertes of Nonwoven Needle Punching Machine for Vegan Leather Application - Muhammad Nabil Najmi Yusjah; Mohd Nazrul Roslan (Progress in Engineering Application and Technology, 2025)
Mechanical characteristics of non-woven textiles made from plant fiber, such as pineapple, bamboo, and banana stem, employing needle punching technology to promote environmentally friendly textile industry practices. Fiber extraction, mixing with cotton and polyester, and processing into non-woven composites are all methodically examined in this study. Thorough mechanical and physical testing is then conducted. The findings emphasize the impact of fiber type and blend composition on performance, showing that pineapple-polyester blends have the highest tearing resistance while banana-cotton composites have the best tensile strength and elongation. The results demonstrate that these plant-based non-wovens have promising durability and structural integrity, which makes them suitable substitutes for vegan leather and other uses. This encourages waste valorization and environmental sustainability in the production process.